Relationship between gut microbiota and multiple sclerosis: a scientometric visual analysis from 2010 to 2023 - Ouyang, Qingrong; Yu, Hao; Xu, Lei; Yu, Ming; Zhang, Yunwei (Frontiers in Immunology, 2024)
Background: Numerous studies have investigated the relationship between gut microbiota (GM) and multiple sclerosis(MS), highlighting the significant role of GM in MS. However, there is a lack of systematic Scientometric analyses published in this specific research area to provide an overall understanding of the current research status.Methods: Perform a scientometric analysis on research conducted between 2010 and 2023 concerning the link between GM and MS using quantitative and visual analysis software (CiteSpace and VOSviewer.)Results: From January 1, 2010, and December 31, 2023, a total of 1019 records about GM and MS were retrieved. The number of publications exhibited a consistent upward trend annually. The United States led in publications, showed the strongest level of collaboration among countries. The University of California, San Francisco stands as the top institution in terms of output, and the most prolific and cited authors were Lloyd H. Kasper and Javier Ochoa-Reparaz from the USA. The research in this field primarily centers on investigating the alterations and associations of GM in MS or EAE, the molecular immunological mechanisms, and the potential of GM-based interventions to provide beneficial effects in MS or EAE. The Keywords co-occurrence network reveals five primary research directions in this field. The most frequently occurring keywords are inflammation, probiotics, diet, dysbiosis, and tryptophan. In recent years, neurodegeneration and neuropsychiatric disorders have been prominent, indicating that the investigation of the mechanisms and practical applications of GM in MS has emerged as a current research focus. Moreover, GM research is progressively extending into the realm of neurodegenerative and psychiatric diseases, potentially becoming future research hotspots.Conclusions: This study revealed a data-driven systematic comprehension of research in the field of GM in MS over the past 13 years, highlighted noteworthy research within the field, provided us with a clear understanding of the current research status and future trends, providing a valuable reference for researchers venturing into this domain.